The Influence of Consumers, Marketing, Prices, Packaging, and Taste Quality on Sales toward Banana Bolen MSME Products in Lamongan - Ali Fathoni; Danu Kusbandono; Ival Milatul Chanifah; Puguh Cahyono (Cita konsultindo, 2022)
In today's business world, many new food products are emerging, one of which is banana cake. This study aims to determine whether consumers, marketing, price, packaging, and taste quality on sales of MSME products, bolen banana Lamongan. The research method used is a quantitative method that contains facts and figures. Data were collected by distributing questionnaires. The sample in this study, namely the customer bolen bananas for 4 months from February 2022 to May 2022, a sample of 75 respondents was obtained. The results showed that the equation Y=5,292-0.123-0.016-0.003-0.008+e which means that the variables independent is X1,X2,X3,X4 do not have a positive value or have no effect on the dependent variable while the X5 variable has a positive value which means it has an effect on the value variable dependent